(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The present work focuses on the study of the application of abundant and less expensive materials such as chitosan and bentonite/chitosan biocomposite in the removal of hexavalent chromium. Spectroscopic analysis like techniques FTIR, XRD and BET have been used to characterize the adsorbents. The data indicate that the adsorption of chromium proceeds kinetically according to a pseudo-second order model on both samples and the apparent activation energy (Ea) have been measured to be 22.9 kJ.mol−1 and 84.4 kJ.mol−1 for chitosan and 5%Bt/CS, respectively. The adsorption isotherm experiments show that the adsorption capacity depends on the studied chromium adsorption temperature. It has been found that the data could be well described by the Langmuir as well as the Freundlich models. Thermodynamic parameters (i.e., change in the free energy (DG°), the enthalpy (DH°), and the entropy (DS°) have been also, evaluated.